The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1590/1807-57622015.0963
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa Nacional de Saúde Bucal (Projeto SBBrasil 2010): que propõem os coordenadores para futuros inquéritos?

Abstract: O objetivo deste artigo é analisar as sugestões dos profissionais que atuaram como coordenadores da Pesquisa Nacional de Saúde Bucal (Projeto SBBrasil 2010) para futuros inquéritos na mesma área. Trata-se de um estudo transversal, com abordagem qualitativa. Os dados foram coletados por meio de um questionário eletrônico e semiestruturado. Os participantes eram profissionais do Sistema Único de Saúde (SUS) e docentes que atuaram como coordenadores do SBBrasil 2010. As respostas foram categorizadas segundo a aná… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(18 reference statements)
0
2
0
1
Order By: Relevance
“…Calibration using the in vivo examination method has been recommended because this method reflects the reality of fieldwork data collection more accurately and simulates the severity of the oral conditions that will be found in the survey. However, previous surveys have criticized the calibration using the in vivo examination method and suggested that there was space to improve the calibration process 28 . Calibration using the in vivo examination method requires a large number of participants, and discomfort is caused due to repeated dental examinations 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calibration using the in vivo examination method has been recommended because this method reflects the reality of fieldwork data collection more accurately and simulates the severity of the oral conditions that will be found in the survey. However, previous surveys have criticized the calibration using the in vivo examination method and suggested that there was space to improve the calibration process 28 . Calibration using the in vivo examination method requires a large number of participants, and discomfort is caused due to repeated dental examinations 14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, previous surveys have criticized the calibration using the in vivo examination method and suggested that there was space to improve the calibration process. 28 Calibration using the in vivo examination method requires a large number of participants, and discomfort is caused due to repeated dental examinations. 14 Moreover, calibration using the in vivo examination method depends upon extensive efforts from volunteers and examiners, as well as a considerable amount of time to perform the examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Na comparação dos resultados do levantamento epidemiológico de saúde bucal no ano de 2003 e 2010 referente a avaliação da necessidade de próteses dentárias, constatou-se que nos adultos de 35 a 44 anos de idade houve aumento da necessidade de prótese no arco superior e redução no arco inferior e em idosos, houve um aumento na necessidade de prótese nos dois arcos20 . No Brasil, 15,4% dos idosos de 65 a 74 anos de idade necessitam de prótese total em ambos os arcos dentários e 17,9% necessitam de prótese total em um dos arcos21 . Estas informações justificam os resultados encontrados no presente estudo referente ao tipo de próteses que são produzidas no estado da Bahia, com maior percentual para prótese total.…”
unclassified